A Comparison of the Effects of Curriculum Learning Experiences on Problem-Solving Efficacy between the University of Science and the University of Social Sciences and Humanities Students - Duong, Minh-Quang (SOSIOHUMANIKA, 2012)
ABSTRACT: Problem-solving is a cognitive process. Many studies show that curriculum has a profound effect on student achievement and plays a crucial role in enhancing studentsâ problem-solving efficacy. The primary purpose of the present study investigated studentsâ problem-solving efficacy at Science and Social Sciences and Humanities Universities and conducted to explore how studentsâ problem-solving efficacy at the two universities was affected by their curriculum learning experiences. The study used a questionnaire survey with 312 students from two member universities at Vietnam National University of Ho Chi Minh City. Results of this study described that studentsâ problem-solving efficacy at the both universities was within the range of âaverageâ to âhighâ response. Curriculum emphasis and learning engagement within two types of institutions indicated positive effect on their problem-solving efficacy.KEY WORD: Curriculum learning experiences, problem-solving efficacy, Vietnamese university students.Â IKHTISAR: Pemecahan masalah merupakan proses kognitif. Banyak kajian menunjukan bahwa kurikulum memiliki pengaruh yang sangat besar pada pencapaian prestasi mahasiswa dan memainkan peran sangat penting dalam meningkatkan kemanjuran pemecahan masalah. Tujuan utama kajian ini menyelidiki kemanjuran pemecahan masalah di bidang IPA (Ilmu Pengetahuan Alam) dan Ilmu-ilmu Sosial dan Kemanusiaan serta dilaksanakan untuk menyelidiki bagaimana kemanjuran pemecahan masalah mahasiswa di kedua bidang dipengaruhi oleh pengalaman belajar kurikulum mereka. Kajian ini menggunakan survey kuesioner dengan 312 mahasiswa dari dua bidang di Universitas Nasional Ho Chi Minh City di Vietnam. Hasil kajian menggambarkan bahwa kemanjuran pemecahan masalah mahasiswa di kedua bidang tersebut berada dalam tingkat respon ârata-rataâ hingga âtinggiâ. Penekanan kurikulum dan keterlibatan pembelajaran dalam dua jenis bidang tersebut menunjukan pengaruh positif pada kemanjuran pemecahan masalah.KATA KUNCI: Pengalaman belajar kurikulum, kemanjuran pemecahan masalah, mahasiswa universitas di Vietnam.About the Author: Minh-Quang Duong is a Lecturer at the Faculty of Education, University of Social Sciences and Humanities, Vietnam National University of Ho Chi Minh City, No.10-12, Dinh Tien Hoang Stress, Ho Chi Minh City, Vietnam; and now as Ph.D. Student at the Department of Educational Policy and Administration, National Chi Nan University, Taiwan (ROC). He can be reached at: flowerfour84_dl@yahoo.comÂ How to cite this article? Duong, Minh-Quang. (2012). âA Comparison of the Effects of Curriculum Learning Experiences on Problem-Solving Efficacy between the University of Science and the University of Social Sciences and Humanities Studentsâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.5, No.2 [November], pp.175-184. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 22, 2012); Revised (October 24, 2012); and Published (November 20, 2012). Â  Â